Parabacteroides distasonis: intriguing aerotolerant gut anaerobe with emerging antimicrobial resistance and pathogenic and probiotic roles in human health - Ezeji, Jessica C. (Gut Microbes, 2021)
Parabacteroides distasonis is the type strain for the genus Parabacteroides, a group of gram-negative anaerobic bacteria that commonly colonize the gastrointestinal tract of numerous species. First isolated in the 1930s from a clinical specimen as Bacteroides distasonis, the strain was re-classified to form the new genus Parabacteroides in 2006. Currently, the genus consists of 15 species, 10 of which are listed as 'validly named' (P. acidifaciens, P. chartae, P. chinchillae, P. chongii, P. distasonis, P. faecis, P. goldsteinii, P. gordonii, P. johnsonii, and P. merdae) and 5 'not validly named' (P. bouchesdurhonensis, P. massiliensis, P. pacaensis, P. provencensis, and P. timonensis) by the List of Prokaryotic names with Standing in Nomenclature. The Parabacteroides genus has been associated with reports of both beneficial and pathogenic effects in human health. Herein, we review the literature on the history, ecology, diseases, antimicrobial resistance, and genetics of this bacterium, illustrating the effects of P. distasonis on human and animal health.